Circulating NETs enable early identification of thrombotic risk in sepsis at emergency care onset - Tejada, Sofia; Clemente, Antonio; Socias, Antonia; Aranda, Maria; del Castillo, Alberto; Mena, Joana; Ribas, Joana Mª; Martín, Luisa; Llerena, Karla Milagritos; Arellano, María Magdalena; Agudo, Miguel; de la Rica, Roberto; et al. (Frontiers in Immunology, 2025)
IntroductionSepsis involves a dysregulated host response to infection and is frequently complicated by coagulopathy, contributing to organ dysfunction and mortality. Early detection of coagulation disturbances in the emergency department (ED) remains clinically challenging. Neutrophil extracellular traps (NETs) have emerged as key mediators linking inflammation and thrombosis in sepsis, yet their prognostic value during early care is unclear. This study aimed to assess whether circulating NETs measured at sepsis onset are associated with inflammatory biomarkers, sepsis-induced coagulopathy (SIC) status, and clinical outcomes.MethodsWe conducted a retrospective study including 212 adult patients with sepsis recruited at the ED presentation. Plasma NETs, IL-6, and MR-ProADM were measured by ELISA. The ISTH SIC score was used to identify early-stage coagulopathy.ResultsCirculating NETs were detected in 61 patients (28.8%) and higher NETs levels were significantly associated with elevated D-dimer, LDH, IL-6, PCT, and hypocholesterolemia. NETs positive patients had increased odds of positive blood cultures (OR = 2.3; 95% CI: 1.2–2.5), thromboembolic events (OR = 4.4; 95% CI: 1.0–19.0), and SOFA ≥ 5 (OR = 2.0; 95% CI: 1.1–2.9). Among 202 patients with complete data to SIC evaluation, 49% met SIC criteria. Although NETs were not independently associated with SIC, their inflammatory and clinical impact was significantly amplified in SIC-positive patients, suggesting a synergetic interaction between NETosis and early coagulopathy.DiscussionNETs quantification at ED presentation may help identify a high-risk immunothrombotic phenotype in sepsis and support earlier NETosis-targeted therapies alongside anticoagulation.